Problematika Penanaman Nilai-Nilai Karakter saat Pembelajaran Masa Pandemi Covid-19 di PKBM (Pusat Kegiatan Belajar Masyarakat - Sehadun, Fransiskus; Dayati, Umi; Al Atok, Rosyid (Universitas Negeri Malang, 2023)
This study aimed to describe the problems of instilling character values in online learning during the COVID-19 pandemic. The approach used is qualitative with case studies. The research results show that the character of students during the pandemic learning period faced problems including a lack of discipline and responsibility. Problems with instilling character values during learning are: not having found the right character education method, low response from Package C students, poorly understood material, limited facilities and infrastructure supporting online learning, and difficulty adjusting the learning schedule for all students.